Larval trypanorhynchs (Platyhelminthes: Eucestoda: Trypanorhyncha) from black-scabbard fish, Aphanopus carbo and oceanic horse mackerel, Trachurus picturatus in Madeira (Portugal) - Costa G.; Veltkamp C.J.; Chubb J.C. (Parasite, 2003)
Four different types of trypanorhynch postlarvae were found attached to the stomach mucosa, external stomach wall or free in the body cavity of two marine fishes from Madeira, namely black-scabbard fish, Aphanopus carbo and oceanic horse mackerel, Trachurus picturatus. Morphological features shown by SEM indicated that the postlarvae belonged to the species Tentacularia coryphaenae, Sphyriocephalus tergestinus, Nybetinia lingualis and possibly N. yamagutii. Prevalence [mean intensity (range)] of T. coryphaenae, S. tergestinus and Nybetinia spp. in A. carbo (n = 135) was 12.6 % [1.65 ± 1.27 (1-6)], 5.9 % [1.57 ± 0.79 (1-3)] and 2.2 % [1.33 ± 0.58 (1-2)] respectively. The prevalence of T. coryphaenae and S. tergestinus showed some seasonality, with a rise in prevalence of T. coryphaenae corresponding to a decrease in prevalence of S. tergestinus. However these differences were not significant. In T. picturatus (n = 304) only N. lingualis was found at a prevalence of 9.6 %. Both S. tergestinus and N. lingualis were recovered only from the stomach mucosa or external stomach wall, while T. coryphaenae was observed either attached to the stomach mucosa or free in the visceral cavity of the fish. The paper presents the first scanning electron micrographs (SEM) of Sphyriocephalus tergestinus and a new geographical record of N. lingualis in T. picturatus